Playing with place in early childhood: An analysis of dark emotion and materiality in children's play. (June 2017) - Procter, Lisa; Hackett, Abigail
In this article, the authors bring together the cultural studies of emotion with theories that foreground the agency of place and objects in order to analyse the entanglement of place, children and emotion (particularly fear) in children's play encounters. When children, objects and places come into play with each other, intensities and emotions emerge. Through an analysis of examples from two ethnographic studies in which play encounters between children and place seem to evoke fear, the authors explore the potentialities of what is evoked. Fear is bounded in place and experienced materially and bodily. As fear becomes entangled in the materiality of place and bodies, emotions work to characterise and categorise bodies (human and non-human) in ways that connect to anthropocentric and colonial metanarratives of animal/human and victim/aggressor. The authors make the case that the cultural studies of emotion can offer a means through which it is possible to connect the micro and the macro, working at these different scales in order to consider the political implications of reconceptualising play encounters through new materialism.